Sunni Ideology, Contention and the Islamic State in Iraq - Fabio Merone (Coordinamento SIBA, 2021)
This article discusses the emergence, development and trajectory of ISIS in Iraq through the lenses of Social Movement Theory. It deploys the political process model and outlines both structural and agency factors. The article argues that the Sunni regions of Iraq developed a separate political community after 2003, against the backdrop of the sectarian politics that the coalition of Shia parties that supported the al-Maliki government in Baghdad were perceived to be pursuing. The political process unfolded in three phases from 2003 to 2014. While Sunni political parties tried to compromise with the al-Maliki government in 2010, the latter's uncompromising stance created the context for more radical forces to come on the scene. In 2013, Baathists and Salafi-jihadists formed a revolutionary front, which led to a generalised uprising in the Sunni regions of the country. The article explains how ISIS was able to take advantage of the political opportunities on the ground and provides analytical insights for its transformation from an isolated organisation to a hegemonic revolutionary force.